(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2000)
A combined multidisciplinary approach has been applied to calculate minimum values of the stratigraphic completeness and, secondarily, sedimentation rates in 9.2 m thick Rosso Ammonitico facies from central Apennines (Italy) and 11 m thick deposits of the same facies in Southern Spain. Middle - Upper Toarcian expanded sedimentation in Valdorbia section (Umbria-Marche Apennines) and extremely condensed Oxfordian-Tithonian sedimentation at Puerto Escaño section (External Subbetic) have been investigated using combined taphonomic, ichnologic and sedimentologic data and analyses. At Valdorbia, infaunal tiering is largely preserved and 27 horizons of infaunal-tiering truncation and casting reveal strong erosional activity forced by tempestite/turbidite events. Therefore, microstratigraphic gaps could be evaluated without biostratigraphic control. In this expanded section, 13 horizons of firm- and hardgrounds have been recorded showing simple or gradational tiering. Conversely, in the condensed Puerto Escaño section, taphonomic analysis reveals 25 horizons of bioclasts truncation (mainly in ammonites), and 56 horizons of firm-hardgrounds intensively bioturbated. In Valdorbia rather than in Puerto Escaño section, the evaluation of flattening in burrows and spherical bioclasts reveal a measurable mechanical compaction and dissolution. In addition, Rosso Ammonitico at Valdorbia section favoured the calculation of decompaction coefficients (nd) for each lithology easier than in Puerto Escaño section. In condensed and essentially hiatal Rosso Ammonitico, mottled deposits due to intense bioturbation dominate and tiering cannot be recognizable. This fact is accentuated by usual overprinting of elementary depositional events, which in turn hampered the accurate calculation of missing deposits. Therefore, in condensed Rosso Ammonitico the latter was only available in terms of minimal missing-record trough the analysis of truncated bioclasts.